2022
DOI: 10.1093/jb/mvac095
|View full text |Cite
|
Sign up to set email alerts
|

Differential interactions of α-synuclein conformers affect refolding and activity of proteins

Abstract: The accumulation of protein aggregates as intracellular inclusions interferes with cellular protein homeostasis leading to protein aggregation diseases. Protein aggregation results in the formation of several protein conformers including oligomers and fibrils, where, each conformer has its own structural characteristic and proteotoxic potential. The present study explores the effect of alpha-synuclein (α-syn) conformers on the activity and spontaneous refolding of firefly luciferase. Of the different conformer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Over-expression of wild type human SNCA has been shown to rescue the phenotypes of mice lacking the synaptic chaperone cysteine string protein suggesting a direct or indirect interaction between these proteins 32 . In other studies, Snca has also been shown to enhance SNARE assembly at the synapse in mice and additional mechanisms of toxicity, including inhibition of ER to Golgi trafficking, have also been proposed 23,[25][26][27][28][33][34][35][36] . Other functions of SNCA, in mitochondrial dynamics and structure, regulation of gene expression, epigenetic programming, nuclear transport, neuron survival, cytoskeletal stabilization and DNA repair, have also been reported (Table 1).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Over-expression of wild type human SNCA has been shown to rescue the phenotypes of mice lacking the synaptic chaperone cysteine string protein suggesting a direct or indirect interaction between these proteins 32 . In other studies, Snca has also been shown to enhance SNARE assembly at the synapse in mice and additional mechanisms of toxicity, including inhibition of ER to Golgi trafficking, have also been proposed 23,[25][26][27][28][33][34][35][36] . Other functions of SNCA, in mitochondrial dynamics and structure, regulation of gene expression, epigenetic programming, nuclear transport, neuron survival, cytoskeletal stabilization and DNA repair, have also been reported (Table 1).…”
Section: Introductionmentioning
confidence: 91%
“…The basis of SNCA toxicity in PD is not well understood; human mutations that have been identified include both loss-of-function (rare missense mutations) and gainof-function (numerical variant) mutations [20][21][22][23] . One potential mechanism for toxicity includes a slow build-up of a distinct wildtype or mutant oligomer; 24 however, the mechanism and identity of the toxic form is not known and continues to be a subject of debate 23,[25][26][27][28] . Clearly, SNCA can form a variety of oligomeric structures, including the fibrils found in Lewy bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly α-synuclein monomers, oligomers and fibrils exert a differential effect on the folding and refolding of other proteins. Bagree et al [ 45 ] examined their influence on the conformation, enzymatic activity and other properties of firefly luciferase. α-Synuclein monomers delayed the inactivation of luciferase under thermal stress conditions and enhanced the spontaneous refolding, whereas oligomers and fibrils adversely influenced luciferase activity and refolding.…”
Section: α-Synuclein Misfolding Aggregation and Fibrillationmentioning
confidence: 99%
“…X-ray crystallography, nuclear magnetic resonance spectroscopy, and cryo-electron microscopy have been used to experimentally determine protein structures. Nevertheless, these techniques primarily provide the most prevalent structures of proteins under specific experimental conditions, often overlooking the coexistence of their structural isomers. Although these isomers may be of minor significance in a cell, under certain circumstances, they may transform into misfolded conformations, ultimately giving rise to pathogenic proteins such as oligomers, fibrils, or aggregates. , …”
mentioning
confidence: 99%
“…Although these isomers may be of minor significance in a cell, under certain circumstances, they may transform into misfolded conformations, ultimately giving rise to pathogenic proteins such as oligomers, fibrils, or aggregates. 7,8 The presence of structural isomers of proteins has been demonstrated in the gas phase by ion mobility mass spectrometry (IMS). 9 This methodology provides information on the relative abundance and overall structures of these isomers by comparing the experimental collision cross sections (CCS) with theoretical ones.…”
mentioning
confidence: 99%